Carriage of Salmonella spp. and Escherichia coli by house flies at three eateries around Universiti Putra Malaysia (UPM) and three poultry farms in Selangor - Julian, E Alvwina (2017)
House flies are of public health concern for their high potential to be carriers of communicable diseases to both human and animals. There is an urgency to explore if the house flies can carry disease–causing bacteria in their gastrointestinal tract that can greatly amplify the risk of human and animal exposure to diseases. The aim of the present study is to study the carriage of Salmonella spp. and Escherichia coli by house flies collected from three local eateries that are frequented by students and staffs of University Putra Malaysia (UPM) and from another three poultry farms in Selangor. This study also aims to investigate the evidence of antibiotic resistance of the isolated bacteria. A total of 60 samples of house flies were caught using sticky papers from three local eateries around UPM and three poultry farms in Selangor. The finding reveals only 3.33% of the total 60 house flies samples collected from both eateries and poultry were confirmed positive for Salmonella spp. The positive samples were shown to exhibit antibiotic resistance towards Amoxicillin. This study also revealed that 56.67% of the total 60 house flies samples caught from the three local eateries around UPM and three poultry farms in Selangor carry Escherichia coli.Most of the Escherichia coli isolateswere found to be resistant to Amoxicillin, Streptomycin and Ceftriaxone. House flies are evidently proven to be able to carry both Salmonella spp. and Escherichia coli and these bacteria do potentially carry antibiotic resistance gene based on the resistant patterns exhibited.